Numerical modeling of two-dimensional delamination growth in composite laminates with in-plane isotropy. (1st June 2021) - Wang, Congzhe; Vassilopoulos, Anastasios P.; Keller, Thomas
Highlights: The 2D Mode I fracture behavior of composite laminates was investigated. Cohesive elements were employed to model the fiber bridging. The pre-crack shape mainly affected the initiation and early propagation stages. The loading zone shape mainly affected the crack shape during stable propagation. The fracture resistance affected both stiffness and fracture response. Abstract: The two-dimensional (2D) delamination growth in fiber-reinforced polymer (FRP) laminates with in-plane isotropy under Mode I loading condition was numerically investigated using finite element analyses. Two sizes of plate models were developed, focusing on different fracture stages. Cohesive elements were employed to simulate the fracture behavior in the presence of large-scale bridging (LSB). The influences of the pre-crack shape/area, loading zone shape/area and fracture resistance were parametrically studied. It was found that either a flatter pre-crack shape or a flatter loading zone shape could result in higher initial structural stiffness and less uniform distribution of the strain energy release rate (SERR) along the pre-crack perimeter during crack initiation and early propagation. However, they had only a minor effect on the stiffness after full fiber bridging development in all directions. The plates finally achieved constant stiffness, which increased linearly with the fracture resistance. The final crack shape was dependent on the loading zone shape and area, but the effects were relatively weak.